Dampak Self Efficacy, Moral Intention Dan Budaya Etis Organisasi Terhadap Whistleblowing Intention - Hidayatul Khusnah; Rimatul Jannah (Universitas Muhammadiyah Malang, 2021)
The purpose of this study was to investigate the influence of Self Efficacy, Moral Intention and Organizational Ethical Culture on Whistleblowing Intention. The data used in this study are primary data obtained through distributing questionnaires to respondents, namely external auditors who work in public accounting firms in Surabaya. The sampling method uses non-probability sampling with saturated sampling technique. The sample consists of 33 external auditors who work in the Public Accounting Firm in Surabaya. The analytical tool used to test the hypothesis is multiple linear regression analysis. The results showed that self-efficacy, moral intention, and organizational culture simultaneously had a positive effect on whistleblowing intention. Self-efficacy and moral intention partially do not affect whistleblowing intention, while organizational ethical culture partially has a positive effect on whistleblowing intention.